IMPROVING THE COMMUNITY ECONOMY THROUGH TECHNOLOGY OF PROCESSING MORINGA LEAVES: PENINGKATAN EKONOMI MASYARAKAT MELALUITEKNOLOGI OLAHAN DAUN KELOR - Baihaqi; Rianse, Muhammad Iqbal Kusumabaka; Sri Rejeki; Mariani L; RH Fitri Faradilla; Ilian Elvira; Aprita, Ika Rezvani; Sri Agustina (PT. ROCE WISDOM ACEH, 2025)
Improving community welfare is the main focus of community service programs, one of which is through the use of Moringa oleifera leaves which are rich in nutrients and have high economic potential. This research was conducted in Labulo Village, Wakorumba District, North Buton Regency, where the majority of the population depends on the agricultural sector. Even though the potential of Moringa leaves is great, public knowledge about its processing is still limited. Therefore, counseling and training regarding Moringa leaf processing technology is very important. This activity aims to provide understanding and skills to the public in processing Moringa leaves into high-value products, such as Moringa leaf powder and Moringa tea. The methods used include material preparation, outreach, practical training, as well as introduction to marketing and product packaging aspects. The evaluation results showed an increase in community knowledge from 45% in the pre-test to 85% in the post-test, and 85% of participants felt confident to continue processing independently. This activity not only has a positive impact on increasing knowledge and skills but also opens up new business opportunities that can increase people's income and welfare. With this program, it is hoped that the community can utilize the potential of the Moringa plant optimally and make it a sustainable source of income. The sustainability of this program needs to be supported by mentoring and monitoring activities to ensure further business development.